Protective effects of exogenous melatonin therapy against oxidative stress to male reproductive tissue caused by anti-cancer chemical and radiation therapy: a systematic review and meta-analysis of animal studies - Dehdari Ebrahimi, Niloofar; Sadeghi, Alireza; Shojaei-Zarghani, Sara; Shahlaee, Mohammad Amin; Taherifard, Erfan; Rahimian, Zahra; Eghlidos, Zahra; Azarpira, Negar; Safarpour, Ali Reza (Frontiers in Endocrinology, 2023)
1.1 Background Male testicular dysfunction is a considerable complication of anti-cancer therapies, including chemotherapy and radiotherapy, partly due to the increased oxidative stress caused by these treatments. Melatonin is an effective antioxidant agent that protects testicles against physical and toxic chemical stressors in animal models. This study aims to systematically review the melatonin's protective effects against anti-cancer stressors on rodential testicular tissue. 1.2 Materials and Method An extensive search was conducted in Web of Science, Scopus, and PubMed for animal studies investigating exogenous melatonin's protective effects on rodent testicles exposed to anti-cancer chemicals and radiotherapeutic agents. Using the DerSimonian and Laird random-effect model, standardized mean differences and 95% confidence intervals were estimated from the pooled data. The protocol was prospectively registered in the International Prospective Register of Systematic Reviews (PROSPERO: CRD42022355293). 1.3 Results The meta-analysis included 38 studies from 43 studies that were eligible for the review. Rats and mice were exposed to radiotherapy (ionizing radiations such as gamma- and roentgen radiation and radioactive iodine) or chemotherapy (methotrexate, paclitaxel, busulfan, cisplatin, doxorubicin, vinblastine, bleomycin, cyclophosphamide, etoposide, Taxol, procarbazine, docetaxel, and chlorambucil). According to our meta-analysis, all outcomes were significantly improved by melatonin therapy, including sperm quantity and quality (count, motility, viability, normal morphology, number of spermatogonia, Johnsen's testicular biopsy score, seminiferous tubular diameter, and seminiferous epithelial height), serum level of reproductive hormones (Follicle-Stimulating Hormone and testosterone), tissue markers of oxidative stress (testicular tissue malondialdehyde, superoxide dismutase, glutathione peroxidase, catalase, glutathione, caspase-3, and total antioxidant capacity), and weight-related characteristics (absolute body, epididymis, testis, and relative testis to body weights). Most SYRCLE domains exhibited a high risk of bias in the included studies. Also, significant heterogeneity and small-study effects were detected. 1.4 Conclusion In male rodents, melatonin therapy was related to improved testicular histopathology, reproductive hormones, testis and body weights, and reduced levels of oxidative markers in testicular tissues of male rodents. Future meticulous studies are recommended to provide a robust scientific backbone for human applications.